Veterinary medicine : a textbook of the diseases of cattle, sheep, pigs, goats, and horses - Radostits, O. M.; Done, Stanley H. (New York : Elsevier Saunders, 2007)
The new 10th edition of this well-respected reference includes thoroughly revised and reviewed information with content on new diseases for the most up-to-date information on diseases effecting sheep, pigs, goats, horses, and cattle. Divided into two sections, General Medicine and Special Medicine, the book covers topics ranging from the clinical examination and manifestation of disease in organ systems to specific diseases of the large animal species.Includes important information essential to any large-animal veterinarian, especially those working with horses, cattle, sheep, pigs, or goats.User-friendly format allows the reader to quickly absorb key information.Quick review/synopsis sections for complex diseases make important information easy to find. Features content on major diseases of all countries, including foreign animal and emerging diseases. Completely revised chapters reflect the information from current literature. New chapters address diseases associated with prions and identify important emerging diseases. A new main author who is a recognized authority on internal medicine of ruminant species with extensive clinical experience and scientific publications brings his expertise to this important reference. Includes content from contributing authors who are international authorities on pig diseases, toxicological disease in animals, and diseases associated with artropod parasites. Several new illustrations and sonograms provide up-to-date visual aids for better understanding.
Part 1. General medicine -- 1. Clinical examination and making a diagnosis -- 2. General systemic states -- 3. Diseases of the newborn -- 4. Practical antimicrobial therapeutics -- 5. Diseases of the alimentary tract I -- 6. Diseases of the alimentary tract II -- 7. Diseases of the liver and pancreas -- 8. Diseases of the cardiovascular system -- 9. Diseases of the hemolymphatic and immune system -- 10. Diseases of the respiratory system -- 11. Diseases of the urinary system -- 12. Diseases of the nervous system -- 13. Diseases of the musculoskeletal system -- 14. Diseases of the skin, conjunctivae and external ear -- 15. Diseases of the mammary gland -- Part 2. Special medicine -- 16. Diseases associated with bacteria I -- 17. Diseases associated with bacteria II -- 18. Diseases associated with bacteria III -- 19. Diseases associated with bacteria IV -- 20. Disease associated with bacteria V -- 21. Diseases associated with viruses and chlamydia I -- 22. Diseases associated with viruses and chlamydia II -- 23. Diseases associated with prions -- 24. Diseases associated with rickettsiales -- 25. Diseases associated with algae and fungi -- 26. Diseases associated with protozoa -- 27. Diseases associated with helminth parasites -- 28. Diseases associated with arthropod parasites -- 29. Metabolic diseases -- 30. Diseases associated with nutritional deficiencies -- 31. Diseases associated with physical agents -- 32. Diseases associated with inorganic and farm chemicals -- 33. Diseases associated with toxins in plants, fungi, cyanobacteria, clavibacteria, insects and animals -- 34. Diseases associated with allergy -- 35. Diseases associated with the inheritance of undesirable characters -- 36. Specific diseases of uncertain etiology -- Appendices -- Conversion factors -- Reference laboratory values -- Drug doses: horses and ruminants -- Drug doses: pigs -- Index.
Includes bibliographical references and index.
Keywords: Veterinary medicine; Veterinary Medicine; Animals, Domestic